Synthesis, Characterization and Application of New Polymers Imprinted with Zinc (II) Ions - Zhakina, A.Kh.; Arnt, O.V.; Vassilets, Y.P.; Alzhankyzy, A.; Zhakin, A.M. (Karagandy University of the name of academician E.A. Buketov, 2024)
In this work, molecularly imprinted polymers with zinc imprints and their comparison polymers without imprints were synthesized. A comparative characterization of the physical parameters of the synthesized zincimprinted (ZnIP) and non-imprinted (NIP) polymers was carried out using the methods of elemental analysis, conductometry, scanning electron microscopy, and IR-Fourier spectroscopy. The ability of the resulting polymers to molecularly recognize zinc was evaluated. Based on experimental data on static adsorption, the adsorption capacity of ZnIP and NIP was determined using an atomic emission spectrometer. It was found that ZnIP is characterized by better physical parameters and a higher ability for molecular recognition of zinc compared to NIP. ZnIP with zinc imprints were found to have better sorption capacity for zinc than their reference polymers. The sorption of zinc by molecular imprinted ZnIP is mainly due to the complex formation and pores of the initial carbon product. The synthesized ZnIP have increased porosity. The presence of pores with a diameter <50 nm in ZnIP is associated with voids formed after acid hydrolysis, which is clearly visible in images recorded by scanning electron microscopy. Thus, the possibility of using ZnIP as a selective sorbent has been established.
Keywords: molecularly imprinted polymers; comparison polymer; sodium humate; polyvinyl alcohol; template; zinc; sorption; adsorbent